Innovative data collection methods in criminological research: editorial introduction - Van Daele, Stijn (Crime Science, 2014)
Novel technologies, such as GPS, the Internet and virtual environments are not only rapidly becoming an increasingly influential part of our daily lives, they also have tremendous potential for improving our understanding of where, when and why crime occurs. In addition to these technologies, several innovative research methods, such as neuropsychological measurements and time-space budgets, have emerged in recent years. While often highly accessible and relevant for crime research, these technologies and methods are currently underutilized by criminologists who still tend to rely on traditional data-collection methods, such as systematic observation and surveys. The contributions in this special issue of Crime Science explore the potential of several innovative research methods and novel technologies for crime research to acquaint criminologists with these methods so that they can apply them in their own research. Each contribution deals with a specific technology or method, gives an overview and reviews the relevant literature. In addition, each article provides useful suggestions about new ways in which the technology or method can be applied in future research. The technologies describe software and hardware that is widely available to the consumer (e.g. GPS technology) and that sometimes can even be used free of charge (e.g., Google Street View). We hope this special issue, which has its origins in a recent initiative of the Netherlands Institute for the Study of Crime and Law Enforcement (NSCR) called CRIME Lab, and a collaborative workshop together with the Research consortium Crime, Criminology and Criminal Policy of Ghent University, will inspire researchers to start using innovative methods and novel technologies in their own research